Serum Biomarkers AFP, CEA and CA19-9 Combined Detection for Early Diagnosis of Hepatocellular Carcinoma - Muhammad Ibrahim Alhadi EDOO (Iranian Journal of Public Health, 2019)
Background: We aimed to evaluate the whether AFP levels alone is an adequate screening indicator, or a combination of Generally, alpha-fetoprotein (AFP), CA19-9 and CEA could provide a better diagnostic tool in detecting and screening asymptomatic patients with primary hepatic cancer (PHC), and also evaluate the correlation of degree of differentiation with serum biomarker levels.